Myanmar’s rapid agricultural mechanization: Demand and supply evidence - Win, Myat Thida; Belton, Ben; Zhang, Xiaobo (International Food Policy Research Institute, 2020)
This chapter analyzes recent patterns of agricultural mechanization in Myanmar from the demand side (farms) and the supply side (machinery dealerships). On the demand side, we analyze the historical and current use of machinery in agriculture, based on a survey of rural households conducted in 2016 in the Ayeyarwady delta close to Myanmar’s largest city, Yangon. On the supply side, we draw evidence from a survey of agricultural machinery supply businesses. Myanmar’s agriculture sector has encountered labor shortages and rising wages since 2011 as workers have begun to move to urban industrial and service sectors. Farmers have responded by rapidly substituting machinery for manual labor. In surveyed areas of Ayeyarwady, draft animals used for land preparation have almost disappeared. Of paddy-farming households, 94 percent used machines for land preparation, and only 12 percent still used draft animals. Widespread mechanization of harvesting has also occurred. Half of all sampled paddy-